Perencanaan Strategis Sistem Informasi Pariwisata Menggunakan Metodologi Ward and Peppard - Geraldy Umbu Tey Renggi Deddy; Penidas Fiodinggo Tanaem (STMIK Budi Darma, 2023)
DISPARBUD of East Sumba district is a government agency engaged in tourism and culture. Information and technology systems (IS/IT) are very important tools to support the achievement of the local government's vision and mission. However, until now the tourism development process at DISPARBUD has not been optimal because not all activities are supported by good use of IS/IT and have an impact on performance activities that are not yet effective and efficient. Therefore it is necessary to use good IS/IT. This study aims to make IS/IT strategic planning at DISPARBUD. This study uses the Ward and Peppard method approach which includes SWOT analysis with the addition of the IFE-EFE matrix which is used in evaluating internal and external factors, value chain analysis, Critical Success Factors (CSFs) method and McFarlan Strategic Grid which will produce an overview of IS requirements /IT which can then be formulated as strategic planning within the next 4 (four) years